2014
DOI: 10.1590/0104-07072014001140013
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the forms of care of nurses in the operating room - a construction based on the grounded theory method

Abstract: The aim of this study was to identify forms of care of nurses in the operating room, and describe how context influences the implementation of this care. This is qualitative study, for which data were obtained by means of five interviews with nurses working in the operating room of a public hospital in the municipality of Duque de Caxias, in the Brazilian state of Rio de Janeiro, conducted between August and September of 2010, using a semistructured script. The methodology followed the Grounded Theory method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In a patient care program released by the Association of Perioperative Registered Nurses, the creation of a caring atmosphere by showing empathy to patients was introduced as a useful factor for reducing the anxiety levels of patients in the operating room prior to surgery [9]. Santos et al [10] also suggested that healthcare providers in the operating room should cultivate empathy as part of providing care for patients. Therefore, showing empathy to patients in the operating room seems to have an effect on healthcare provider-patient communications, and teaching this concept to operating room nursing students as would-be personnel in this domain is of the utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…In a patient care program released by the Association of Perioperative Registered Nurses, the creation of a caring atmosphere by showing empathy to patients was introduced as a useful factor for reducing the anxiety levels of patients in the operating room prior to surgery [9]. Santos et al [10] also suggested that healthcare providers in the operating room should cultivate empathy as part of providing care for patients. Therefore, showing empathy to patients in the operating room seems to have an effect on healthcare provider-patient communications, and teaching this concept to operating room nursing students as would-be personnel in this domain is of the utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Article (8) England 2018 the operating room (25) ; and use of instruments to systematize and document nursing practice (4) . The category "factors with negative implications" included: emergency surgery (8,20,22); lack, poor quality or unavailability of equipment (8,16,19,23); problems related to the workflow of inpatient units (8) ; delay and cancellation of surgeries (8,25); excessive movement of the circulating nurse (10) ; lack of human (4,13,16,(19)(20)22) , material (8,13,16,(19)(20)23) and structural (8,13,16,20,22) resources; client's clinical conditions (13,20,22) ; lack of adequate time to carry out activities (16) ; lack of planning (6,16,19) and organization (16,19) ; lack of preoperative evaluation (19) ; technical failures of professionals (19) ; poor quality devices and equipment (19) ; failure to communicate with the management (6) ; work overload (23...…”
Section: Type Of Study/ Level Of Evidence Factor Implicationsmentioning
confidence: 99%
“…In this regard, communication between the surgeon, the anesthesiologist and the nursing team is important (27) . As for communication failures in other areas, (such as management, for example) they make it difficult to carry out work activities (6), which can be reflected in late and/or unilateral decisions that can be harmful in a dynamic context like the operating room.…”
Section: Factors With Negative Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative is understood as the three stages experienced by the patient in relation to the surgical procedure, that is, preoperative (24 prior to the surgery), transoperative/intraoperative and immediate postoperative (24 hours after the surgery) (3) . This professional must ensure a safe practice, so that technological advances do no stay ahead of their essential characteristic, care (4) .…”
Section: Introductionmentioning
confidence: 99%